1963
DOI: 10.1037/h0048903
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bilateral hippocampal lesions in rats.

Abstract: The behavior of 10 rats with bilateral hippocampal lesions was compared with that of 11 cortically damaged and 12 unoperated control Ss in 4 experimental situations. Compared to other groups, hippocampal Ss (a) entered more squares of an open field (p < .01); (b) took more trials to reach criterion on a successive brightness discrimination (p < .01), but showed no deficit on a simultaneous discrimination using the same stimuli; and (c) made more errors on both of 2 Hebb-Williams mazes (p < .01). Both hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
179
9

Year Published

1967
1967
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 465 publications
(218 citation statements)
references
References 13 publications
30
179
9
Order By: Relevance
“…When placed in a situation involving inhibition of movement, rats with hippocampal lesion were unable to inhibit movement to avoid shock, suggesting impairment of passive avoidance behavior [92,93] . In another report, electrical lesions of the hippocampus resulted in increased open-field activity in rats [94] , similar to the hyperactivity observed in the above paper [92] and other previous related experiments [95,96] . Moreover, significant decreases in shock-induced aggression was observed following electrical hippocampal lesions [94] , consistent with previous findings from Blanchard and Blanchard [97] .…”
Section: Electrical Lesionsupporting
confidence: 68%
“…When placed in a situation involving inhibition of movement, rats with hippocampal lesion were unable to inhibit movement to avoid shock, suggesting impairment of passive avoidance behavior [92,93] . In another report, electrical lesions of the hippocampus resulted in increased open-field activity in rats [94] , similar to the hyperactivity observed in the above paper [92] and other previous related experiments [95,96] . Moreover, significant decreases in shock-induced aggression was observed following electrical hippocampal lesions [94] , consistent with previous findings from Blanchard and Blanchard [97] .…”
Section: Electrical Lesionsupporting
confidence: 68%
“…Surgery was done when Ss were 70-95 days old. Lesions were produced by aspiration in one stage under Nembutal (50 mg/kg) anesthesia as described previously (Kimble, 1963). Eleven Sa received bilateral lesions of the hippocampus and overlying cortical tissue, 10 Ss received lesions of just the overlying neocortical tissue, and 11 Ss were unoperated.…”
Section: Methodsmentioning
confidence: 99%
“…, 1969) Pribram findings are studies which report that animals with hippocampal lesions are impaired in discrimination reversal even though the initial discrimination was readily acquired (Kimble, 1967;Thompson & Langer, 1963 (Jarrard & Bunnell, 1968;Leaton, 1967;Sengstake, 1968). Hippocampals have also been shown to lever press at higher rates than controls for a brief flash of light (Kamback, 1967 (Karmos & Gastryan, 1962;Sandwald, et al, 1970), although others have found no deficit in the habituation of the OR even though habituation of activity to a novel environment was impaired (Jarrard & Korn, 1969 (Glazner, 1953 Kimble, 1967;Leaton, 1967;Stevens, 1973 Lubow, 1973;Weiss & Brown, 1974, for reviews).…”
Section: Modelmentioning
confidence: 99%
“…Moore's (1973) (1975) demonstrated that CI can be produced with odor serving as the inhibitory CS, and Moore et al, (1973) Douglas, 1972). Kimble (1963) found It is interesting to note that in the rabbit the formation of a conditioned inhibitor is a much more difficult task than simple differential conditioning (cf., Moore, 1972; Marchant & Moore, 1974 (1927) hypothesized that the cortex was the seat of internal inhibition.…”
Section: Modelmentioning
confidence: 99%